A novel strongly correlated electronic thin-film laser energy/power meter based on anisotropic Seebeck effect - Zhang G.-Y. (2014)
Strongly correlated electronic (SCE) materials including high-temperature superconducting cuprate and colossal magnetoresistance manganite thin films demonstrate tremendous anisotropic Seebeck effect which makes them very promising for developing high-performance laser detectors. In this work, laser-induced thermoelectric voltage (LITV) signals with nanosecond response time have been measured in SCE La1-xPbxMnO3 thin films based on anisotropic Seebeck effect at room temperature. The magnitude of the LITV signals increases linearly with laser energy/power density in a wide range of laser wavelengths from ultraviolet, visible to infrared based on which a novel SCE thin-film laser energy/power meter has been developed. © 2014 Springer-Verlag Berlin Heidelberg.